Issues in disability among adults with cerebral palsy - Gut, Radosław; Jabłoński, Mirosław (Polish Journal of Public Health, 2011)
Introduction. Individuals affected by Cerebral Palsy (CP) may be recognized as distinctive group of attendees of long-term care facilities. Motor disturbances, typical in the group are usually accompanied by various disabilities, requiring specific medical and social support. Aim. The Aim was to determine the incidence of cerebral palsy (CP) among the attendees of long-term care facilities,and to characterise the patients with cerebral palsy (CP). Material and methods. On the basis of medical documentations analysis and screening clinical examination of 435 attendees of Przemyśl district long-term care institutions a group of patients suffering from cerebral palsy was determined and evaluated in regard to quantitative aspects of selected health problems. Results. Thirty five patients meeting the conditions for diagnosing cerebral palsy were identified in two categories of care: "adults with intellectual impairment" (29 people) and "patients with chronic mental disorders" (6 people). The abovementioned patients constituted 27% and 4% of the related groups respectively. Cerebral palsy was mentioned in medical documentation of 10 patients, in 9 cases it had been diagnosed in childhood. Nine of the patients were diagnosed with other locomotion disabilities. Intellectual impairment was identified in the documentation of 29 people (83%), which gives a higher ratio than expected, taking into consideration Polish epidemiologic research. Conclusions. Intellectual impairment, recognized as the main reason for provision of a long-term care,results in placing minor importance or neglecting completely other dysfunctions (including locomotive disabilities) in cerebral palsy patients’ health examinations. The statement that patients with cerebral palsy (CP) constitute and should be recognized as a separate category of attendees of long-term institutions is justified.